Vitamin D deficiency and VDR TaqI polymorphism on diabetic nephropathy risk among type 2 diabetes patients - Melake, Addisu; Mengstie, Misganaw Asmamaw (Frontiers in Endocrinology, 2025)
BackgroundMany studies have shown that vitamin D deficiency and vitamin D receptor TaqI gene polymorphisms are associated with susceptibility to diabetic nephropathy in various populations. The objective of this study was to determine the impact of vitamin D deficiency and vitamin D receptor TaqI gene polymorphism on the risk of diabetic nephropathy complications in T2DM at the Debre Tabor Comprehensive Specialized Hospital, Northwest EthiopiaMethodsA total of 210 participants, including 70 diabetic patients with nephropathy, 70 diabetic patients without nephropathy, and 70 healthy controls, participated in an age—and sex-matched hospital-based case-control study. Demographic and clinical data were assessed to determine the related risk factors. DNA was extracted from blood samples and subjected to polymerase chain reaction and agarose gel electrophoresis analysis to determine the TaqI genotypes.ResultsVitamin D deficiency was detected in our investigation, and it was much more prevalent in diabetic nephropathy patients than type 2 diabetic patients and controls (OR = 5.05, 95% CL = 2.03–12.53; P < 0.001). Moreover, both the TaqI tt genotype (OR: 2.48; 95% CL: 1.15-5.37; P=0.020) and t allele (OR: 1.70; 95% CL: 1.13-2.57; P=0.010) were substantially more prevalent in diabetic nephropathy patients than in type 2 diabetic patients and controls, indicating that it may be a major risk factor for the development of diabetic nephropathy.ConclusionsThe findings point to a potential link between vitamin D deficiency and diabetic nephropathy complications. Moreover, TaqI gene polymorphisms have been linked to an increased risk of developing the disease in the Ethiopian population under study.